2018
DOI: 10.3389/fnins.2018.00759
|View full text |Cite
|
Sign up to set email alerts
|

Sleep/Wake Disruption in a Mouse Model of BLOC-1 Deficiency

Abstract: Mice lacking a functional Biogenesis of Lysosome-related Organelles Complex 1 (BLOC-1), such as those of the pallid line, display cognitive and behavioural impairments reminiscent of those presented by individuals with intellectual and developmental disabilities. Although disturbances in the sleep/wake cycle are commonly lamented by these individuals, the underlying mechanisms, including the possible role of the circadian timing system, are still unknown. In this paper, we have explored sleep/circadian malfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 121 publications
2
25
0
Order By: Relevance
“…Structural analysis of the SCN was performed as previously described ( Lee et al, 2018 ). WT and Cntnap2 KO mice (males, 3–4 mo) were anesthetized with isoflurane at a specific time during the night (ZT 14) and transcardially perfused with phosphate buffered saline (PBS, 0.1 M, pH 7.4) containing 4% ( w / v ) paraformaldehyde (PFA, Electron Microscopy Sciences, Hatfield, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Structural analysis of the SCN was performed as previously described ( Lee et al, 2018 ). WT and Cntnap2 KO mice (males, 3–4 mo) were anesthetized with isoflurane at a specific time during the night (ZT 14) and transcardially perfused with phosphate buffered saline (PBS, 0.1 M, pH 7.4) containing 4% ( w / v ) paraformaldehyde (PFA, Electron Microscopy Sciences, Hatfield, PA).…”
Section: Methodsmentioning
confidence: 99%
“…For Nissl Staining, coronal brain sections (20 μm) were stained with a 1% (w/v) cresyl violet (Sigma-Aldrich Corp., St. Louis, MO) solution as previously reported (Lee et al, 2018). Photographs were acquired on a Zeiss Axioskop equipped with a Zeiss color or monochrome Axiocam using the AxioVision software (Zeiss, Pleasanton, CA) and used to determine the thickness of the cerebral cortex (layers I-VI) in rostral and caudal sections, the outer border and total sectional area of the hippocampus, and the cell density and cytoarchitecture in the Cornu Ammonis (CA)1 subfield of the hippocampus.…”
Section: Histomorphometrical and Immunohistochemical Analysesmentioning
confidence: 99%
“…Interestingly, a small subset of these studies has raised the notion of a putative role for BLOC-1 in mouse brain development. Thus, the levels of both pallidin and dysbindin have been found to be developmentally regulated in the rodent brain (Ghiani et al, 2010;Ito et al, 2010), and lack of BLOC-1 was found to partially impair neurite outgrowth and dendritic spine morphogenesis in vitro (Ghiani et al, 2010;Ito et al, 2010;Ma, Fei, Fu, Ren, & Wang, 2011) as well as neuronal arborization in vivo (Lee et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arrows highlight OL coexpressing the markers. Mice were perfused at Zeitgeber Time (ZT) 6 and double-immunolabelling for O4 or CNPase and Per2 was performed as previously reported [50,51]. PER2 expression can be also appreciated in other neural cells surrounding the O4 positive OL.…”
Section: Ol Intracellular Transcriptional Dynamics Vary With Sleep/wamentioning
confidence: 99%